The amount of macrophages and activated plasma cells on wound healing process affected by spirulina - Regina Purnama Dewi Iskandar; Retno Indrawati; Ira Arundina; Retno Pudji Rahayu (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Spirulina which grows abundantly in tropical seas have been investigated to enhance immune system. The administration of spirulina in tooth extraction sockets was expected to optimise the function of immunocompetent cells. Therefore, wound healing process would be improved. Purpose: The aim of this study was to prove that administration of spirulina could influence immune system in tooth extraction sockets. Method: There were 28 Cavia cobayas used in this study and were put in group of four. Mandibular left incisive were extracted from each of them. The basis made from mixture of polyethylene glycol (PEG) 400 and PEG 4000 was administrated into each socket in control group (TG0). In addition, spirulina 12% was administrated into group TG1, spirulina 24% was administrated into group TG2, and spirulina 48% was administrated into group TG3. All of the Cavia cobaya were decapitated and the jaws were removed in day 5 after tooth extraction. The jaws were decalcified in EDTA solution, formed into paraffin block, processed for hematoxylin and eosin (H & E) and immunohistochemistry staining afterwards. Datas were analysed statistically using Anova method. Result: There was an augmentation in the number of macrophages and activated plasma cells after spirulina application. The administration of higher concentrations of Spirulina leads to greater amount of macrophages and activated plasma cells in each groups. Conclusion: In conclusion, spirulina is able to increase the amount of macrophages and activated plasma cells which play important role in healing process.